Fast Food Consumption Patterns Relationship and Physical Activity with Nutritional status in Adolescents at SMA Dr. Soetomo Surabaya City - Caecilia Betris Oktavianty; Nuning Marina Pengge; Nur Hatijah; Ani Intiyati (Journal of Nutrition Explorations, 2024)
Teenagers need increasing nutritional intake due to experiencing physical changes and transitioning from childhood to adolescence. One of the factors influencing this is their dietary habits and physical activities. The researches objective is to understand the relationship between fast food consumption patterns,physical activities,and Nutritional status among 11th-grade students at SMA Dr. Soetomo in Surabaya City. The research methodology used was an analytical survey design with a cross-sectional approach.The sample consists of 60 respondents.The statistical analysis used in this research was the Spearman's rank correlation.The results of this research,shows that the majority of respondents were 17 years old and categorized as having excessive or overweight Nutritional status. They had poor dietary habits and engaged in very light physical activities. There’s a significant relationship between fast food consumption patterns and Nutritional status (p=0.000),as well as between physical activities and Nutritional status (p=0.042) among 11th-grade students at SMA Dr. Soetomo in Surabaya City.In conclusion,this research reveals a connection between fast food consumption patterns, physical activities, and Nutritional status among 11th-grade students at SMA Dr. Soetomo in Surabaya City,should be made to limit fast food consumption and increase physical activities to reduce overweight and obesity